Nrf2 Activation Protects Against Organic Dust and Hydrogen Sulfide Exposure Induced Epithelial Barrier Loss and K. pneumoniae Invasion - Shrestha, Denusha; Massey, Nyzil; Bhat, Sanjana Mahadev; Jelesijević, Tomislav; Sahin, Orhan; Zhang, Qijing; Bailey, Kristina L.; Poole, Jill A.; Charavaryamath, Chandrashekhar (Frontiers in Cellular and Infection Microbiology, 2022)
Agriculture workers report various respiratory symptoms owing to occupational exposure to organic dust (OD) and various gases. Previously, we demonstrated that pre-exposure to hydrogen sulfide (H2S) alters the host response to OD and induces oxidative stress. Nrf2 is a master-regulator of host antioxidant response and exposures to toxicants is known to reduce Nrf2 activity. The OD exposure-induced lung inflammation is known to increase susceptibility to a secondary microbial infection. We tested the hypothesis that repeated exposure to OD or H2S leads to loss of Nrf2, loss of epithelial cell integrity and that activation of Nrf2 rescues this epithelial barrier dysfunction. Primary normal human bronchial epithelial (NHBE) cells or mouse precision cut-lung slices (PCLS) were treated with media, swine confinement facility organic dust extract (ODE) or H2S or ODE+H2S for one or five days. Cells were also pretreated with vehicle control (DMSO) or RTA-408, a Nrf2 activator. Acute exposure to H2S and ODE+H2S altered the cell morphology, decreased the viability as per the MTT assay, and reduced the Nrf2 expression as well as increased the keap1 levels in NHBE cells. Repeated exposure to ODE or H2S or ODE+H2S induced oxidative stress and cytokine production, decreased tight junction protein occludin and cytoskeletal protein ezrin expression, disrupted epithelial integrity and resulted in increased Klebsiella pneumoniae invasion. RTA-408 (pharmacological activator of Nrf2) activated Nrf2 by decreasing keap1 levels and reduced ODE+H2S-induced changes including reversing loss of barrier integrity, inflammatory cytokine production and microbial invasion in PCLS but not in NHBE cell model. We conclude that Nrf2 activation has a partial protective function against ODE and H2S.